Infrared absorption spectra of a series of 2, 6-diamino and 2-amino-6hydroxy-8-choroalkyl purines - I. M., Ejimadu (Universiti Putra Malaysia Press, 2003)
8-haloalky purines were synthesized and infrared analysis (IR) carried out on them. The syntheses as well as the ill analyses are reported. The purines synthesized and studied include (i) 2,6-diamin-8-Chloromethyl purines, (ii) 2, 6-diamin-8-chlorethyl purine, (iii) 2, 6-diamino-8-chlor$'opyl purine, (iv) 2-amin~6-hydroxyl-8-chloroethyl purine, (v) 2-amin-6-hydroxyl 8-(3-chlor$'opyl) purine. The ultra violet UV lmax absorption oj these purines were taken at /11 and results are presented. The melting points and their elemental analyses are also presented. The IR (infrared in KBr) spectra of C-8 substituted 2, 6-diamino; 2. or 2-amino -6hydroxy purines, 6 are compared to the IR spectra of pteridines 2; E.; benzimidazole, 2; Pyrroles, 10; indole, 11 (Tables I, II, III and figures 1, 2, 3, 5 and 6). Figure 4 is presented to relate these novel purines to (i) natural liver L. casei Jactor (A) (ii) synthetic liver L. cacei factor (Racemic pteroylgutamic acid (C) (v) Synthetic racemic liver L. casei factor, racemic pteraylglutamic acid (D) (iv) Natural racemic liver L. casei factor pteroic acid (E).